PENGARUH PEMBERIAN PENGHARGAAN EKSTRINSIK TERHADAP KINERJA KARYAWAN - Suntari, Esti - (Universitas Pamulang, 2017)
ABSTRACT The objective of this research is to obtain information about the effect of extrinsic rewards to employees performanceThis research used survey method, sample in this research are 56 employees as respondents who as selected used simple random sampling with part analysis.Based on calculation of correlational coefficient on the table above, rxy was 0,659 then it leads to result of correlational coefficient (uji-t) from thitung 6,446 > ttabel=2,397 this means that there is a significant relations between extrinsic rewards to employees performance. Meanwhile with Pearson Product Moment , rxy was 0,659. Hypothesis test was done by (Î±)= 0,05 and sample (n)=56 thitung> t tabel meaning that Ho was rejected. The calculation results the effect of extrinsic rewards to employees performance gives the sense that approximately 43.482% of the variation increased of employees performance is determined and influenced by extrinsic while the rest of the award is determined by other factors. The conclusion of this research are there is a positive direct effect of extrinsic rewards to employees performance. Keywords: extrinsic rewards, performance